Flexible self-supporting supercapacitor electrode material and preparation method thereof
By compounding bamboo carboxylated nanocellulose with TiO2 nanotubes, forming a TiO2/cellulose composite carbon aerogel, and growing Ni1Co3 nanoneedle arrays on it, the problems of poor mechanical properties and low specific capacitance of pure cellulose-based carbon aerogel were solved, and supercapacitor electrode materials with high specific capacity, flexible and certain support capabilities were prepared.
Patent Information
- Application Number
- CN202510313782.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-06-06
AI Technical Summary
When the existing pure cellulose-based carbon aerogel is used as a supercapacitor electrode material, there is a problem that the mechanical properties are poor and the specific capacitance is lower.
Bamboo carboxylated nanocellulose is mixed with TiO2 nanotubes, and after ice bath ultrasonic dispersion, CO2 supercritical drying and pyrolysis treatment, TiO2/cellulose composite carbon aerogel is formed, and a Ni1Co3 nanoneedle array is grown on it to prepare a flexible self-supporting supercapacitor electrode material.
The mechanical properties and specific capacitance of the material are improved, the flexibility and electrochemical properties of the material are ensured, and the high specific capacity and good cycle stability are achieved.
Smart Images

Figure CN120108948A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of supercapacitor electrode materials, and in particular to a flexible self-supporting supercapacitor electrode material and a preparation method thereof. Background Art
[0002] In recent years, in order to adapt to the trend of energy storage devices towards thin, light, miniature and flexible wearable, people have developed many new energy storage devices. Flexible supercapacitors, as an important component of flexible energy storage devices, can ensure continuous and stable energy output under mechanical deformation conditions. The composition of flexible supercapacitors mainly includes electrode materials, diaphragms and electrolytes, and flexible electrodes are the key to determining their performance. Cellulose-based carbon materials are regarded as good self-supporting electrode material substrates due to their rich pore structure and excellent chemical stability, thermal stability, biodegradability and mechanical strength. Its three-dimensional network structure and high specific surface area provide abundant transmission channels and active sites for ions. At the same time, its low density and strong flexibility make the assembled electronic devices have the advantages of light weight, portability, tensile and compressive resistance.
[0003] In practical applications, pure cellulose-based carbon aerogels have the following problems: First, the mechanical properties are poor. When subjected to stretching, bending and extrusion, they will break or even collapse, which greatly hinders their application in flexible devices. Second, carbon aerogels become hydrophobic materials due to the removal of oxygen functional groups during the carbonization process. Its surface is hydrophobic, which is not conducive to the infiltration and penetration of electrolytes, and increases the contact resistance between electrolyte ions and carbon skeletons, resulting in reduced capacitance performance. Third, although cellulose carbon aerogels have excellent high current performance and cycle stability, the material can only form double-layer capacitors, and the maximum capacitance value is much lower than pseudocapacitors. In this regard, researchers have done a lot of work, such as; to solve the problem of poor mechanical properties of carbon aerogels, organic-inorganic hybrid synthesis methods, fiber filler reinforced composites, and polymer reinforced composites are generally used. In order to solve the problem of surface hydrophobicity, hydrophilic functional groups or non-metallic elements such as N, P, S, O and other elements are generally introduced on the surface. In order to increase the specific capacitance of electrode materials, the method of bonding with high specific capacitance materials such as conductive polymers and transition metal oxides is generally adopted. Although the above research has improved some performance problems of carbon aerogel as a supercapacitor electrode material, a large number of problems have not been solved. For example, when the mechanical properties of materials with poor conductivity are enhanced, it leads to difficulties in electron transmission; when the hydrophobicity of the electrode material surface is reduced, the production process is complicated and cumbersome and a large amount of toxic chemicals will be used; when adding high specific capacitance materials, binders are mostly used, which not only increases the mass volume of the electrode, but also separates the active material from the collector after repeated bending, resulting in a sharp drop in capacitance.
[0004] Therefore, there is an urgent need for a flexible self-supporting supercapacitor electrode material and a preparation method and application thereof to solve the above technical problems. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a flexible self-supporting supercapacitor electrode material and a preparation method and application thereof in view of the above-mentioned deficiencies in the prior art, so as to solve the technical problems that traditional pure cellulose-based carbon aerogel has poor mechanical properties and low specific capacitance when used as a traditional capacitor electrode material.
[0006] The present invention first provides a method for preparing a flexible self-supporting supercapacitor electrode material, which is characterized by comprising: S10, bamboo carboxylated nanocellulose solution and TiO 2 The nanotubes were mixed and then dispersed by ultrasonic in an ice bath. TiO 2 / cellulose composite hydrogel; S20, for TiO 2 / cellulose composite hydrogel for CO 2 Supercritical drying treatment to obtain TiO 2 / cellulose composite aerogel; S30, TiO 2 / cellulose composite aerogel was pyrolyzed to obtain TiO 2 / cellulose composite carbon aerogel; S40, TiO 2 / cellulose composite carbon aerogel as substrate for the growth of Ni 1 Co 3 The nanoneedle array is prepared by washing and drying the obtained precipitate to form a flexible self-supporting supercapacitor electrode material.
[0007] Preferably, in step S10: the bamboo carboxylated nanocellulose in the bamboo carboxylated nanocellulose solution is prepared by etherification; the cross-sectional size of the bamboo carboxylated nanocellulose is 5-10 nm, the length is 500-1000 nm, and the aspect ratio is (50:1)-(50:1); the mass fraction of the bamboo carboxylated nanocellulose solution is 2%-3%.
[0008] Preferably, in step S10: TIO 2 The surface of the nanotubes has hydroxyl groups, with an outer diameter of 10~200nm and a length of 1~50um; TiO 2 The mass ratio of nanotubes to bamboo carboxylated nanocellulose is (2~3):10.
[0009] Preferably, in step S10: the ultrasonic dispersion time of the ice bath ultrasonic dispersion treatment is 10 to 30 minutes, and the standing time at room temperature is 12 to 24 hours.
[0010] Preferably, in step S20: CO2 The drying temperature of supercritical drying treatment is 40~45℃, and the drying pressure is 6.0~10.0Mpa.
[0011] Preferably, in step S30: the heating rate of the pyrolysis treatment is 3-5°C / min, the pyrolysis temperature is 550-650°C, and the pyrolysis time is 1-3h.
[0012] Preferably, step S40 specifically includes: 2 / cellulose composite carbon aerogel impregnated with three-dimensional Ni 1 Co 3 The hydroxide nanoneedle precursor is subjected to water bath heating treatment, and the precipitate after the reaction is completed is washed and dried multiple times to obtain a flexible self-supporting supercapacitor electrode material.
[0013] Preferably, TiO 2 / cellulose composite carbon aerogel and three-dimensional Ni 1 Co 3 The mass ratio of the hydroxide nanoneedle precursor is 1: (280~320); the three-dimensional Ni 1 Co 3 The hydroxide nanoneedle precursor is Ni(NO 3 ) 2 6H 2 O、Co(NO 3 ) 2 6H 2 O, urea and water are mixed in a mass ratio of 1:3:(2~4):(100~120); the heating temperature of the water bath heating treatment is 115~125℃, and the heating time is 5~6h.
[0014] Correspondingly, the present invention also provides a flexible self-supporting supercapacitor electrode material, which is prepared by the method for preparing a flexible self-supporting supercapacitor electrode material as described in any one of the above items.
[0015] The beneficial effects of the present invention are as follows: Different from the prior art, the present invention provides a flexible self-supporting supercapacitor electrode material and a preparation method thereof. The preparation method firstly uses bamboo carboxylated nanocellulose as a structural unit to composite TiO 2 Nanotube preparation of TiO 2 / cellulose composite carbon aerogel, TiO 2 / cellulose composite carbon aerogel continues the light weight, high elasticity and stable structure of bamboo cellulose. 2 The addition of nanotubes also improves its mechanical properties and hydrophilicity, while enriching the TiO 2 The micro-mesoporous structure of the carbon aerogel / cellulose composite provides a larger specific surface area and a larger number of micropores for storing charges. 2 / cellulose composite carbon aerogel is then hydrothermally grown to form pseudocapacitor material Ni 1 Co 3 -OH nanoneedles on TiO 2 / cellulose composite carbon aerogel fiber skeleton, and finally prepared a flexible self-supporting supercapacitor electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The three-dimensional Ni provided in the embodiment of the present invention 1 Co 3 -OH@Carbon gas condensation hybrid nanomaterial preparation process flow chart; Figure 2A to Figure 2B The three-dimensional Ni provided in Example 1 of the present invention 1 Co 3 Preparation method of TiO-OH@ carbon gas condensation hybrid nanomaterials 2 SEM image of / cellulose composite carbon aerogel; Figure 3A~Figure 3B The three-dimensional Ni provided in Example 1 of the present invention 1 Co 3 Preparation method of three-dimensional Ni-OH@ carbon gas condensation hybrid nanomaterials 1 Co 3 -OH@C gas condensed hybrid nanomaterials SEM images; Figure 4A The three-dimensional Ni prepared in Example 1 of the present invention 1 Co 3 -OH@carbon gas condensation hybrid nanomaterials cyclic voltammetry curve; Figure 4B The three-dimensional Ni prepared in Example 1 of the present invention 1 Co 3 -OH@Carbon gas condensation hybrid nanomaterial constant current charge and discharge curve; Figure 5 The three-dimensional Ni prepared in Example 1 of the present invention 1 Co 3 -OH@Carbon gas condensation hybrid nanomaterial cycle stability test diagram; Fig. 6A A comparison diagram of nitrogen adsorption / desorption isotherm curves of corresponding samples prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention; Figure 6B A comparison chart of pore size distribution of corresponding samples prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention; Figure 7 Ni prepared in Comparative Example 6 1 Co 3 SEM image of -OH@carbon gas-condensed hybrid nanomaterials. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] The technical problem to be solved by the present invention is to provide a flexible self-supporting supercapacitor electrode material and a preparation method and application thereof in view of the above-mentioned deficiencies in the prior art; when the flexible self-supporting supercapacitor electrode material is applied to the flexible self-supporting supercapacitor electrode material, it has a large specific charge and strong cycle stability.
[0019] In order to achieve the above technical objectives, this application adopts the following technical solutions: First, see Figure 1 , Figure 1 A flow chart of a method for preparing a flexible self-supporting supercapacitor electrode material provided in an embodiment of the present invention; wherein the flexible self-supporting supercapacitor electrode material is TiO 2 Nanotubes are used as reinforcing materials. The surface hydroxyl groups are tightly connected with the carboxyl groups in the high-strength and high-elastic bamboo nanocellulose through esterification reaction. TiO 2 / cellulose composite aerogels, and TiO 2 Growth of Ni on the network skeleton of / cellulose composite carbon aerogel 1 Co 3 The above-prepared flexible self-supporting supercapacitor electrode material has the characteristics of high specific capacitance, flexibility and certain supporting capacity.
[0020] In an embodiment of the present invention, the method for preparing the above-mentioned flexible self-supporting supercapacitor electrode material specifically includes: S10, bamboo carboxylated nanocellulose solution and TiO 2 The nanotubes were mixed and then dispersed by ultrasonic in an ice bath. TiO 2 / cellulose composite hydrogel.
[0021] Specifically, step S10 also includes: Firstly, a bamboo carboxylated nanocellulose solution with a mass fraction of 2% to 3% was prepared by etherification method. The cross-sectional size of the bamboo carboxylated nanocellulose was 5 to 10 nm, the length was 500 to 1000 nm, and the aspect ratio was (50:1) to (50:1).
[0022] Secondly, provide TiO 2 Nanotubes, TiO2 The outer diameter of the nanotubes is in the range of 10~200nm, and the length is in the range of 1~50um. Its surface is rich in hydroxyl groups and can be transformed from an amorphous state to anatase at 550~650℃.
[0023] Finally, the bamboo carboxylated nanocellulose solution and TiO 2 The nanotubes were mixed after magnetic stirring, and then ultrasonically dispersed for 10 to 30 minutes by an ultrasonic cell disruptor under ice bath, and allowed to stand at room temperature for 12 to 24 hours to obtain TIO. 2 / cellulose composite hydrogel. Among them, TiO 2 The mass ratio of nanotubes to bamboo carboxylated nanocellulose in the bamboo carboxylated nanocellulose solution is (2~3):10.
[0024] Specifically, bamboo carboxylated nanocellulose, as a natural polymer material, has high specific surface area, light weight, high elasticity and biocompatibility, but its conductivity is poor. 2 Nanotubes have excellent electrical properties, photocatalytic activity and mechanical strength, but they are relatively brittle. 2 Nanotubes can maintain the flexible skeleton of cellulose while utilizing TiO 2 The rigidity enhances the mechanical properties of the composite material and introduces a conductive network.
[0025] S20, for TiO 2 / cellulose composite hydrogel for CO 2 Supercritical drying treatment to obtain TiO 2 / cellulose composite aerogel.
[0026] Specifically, step S20 also includes: TiO was prepared by autoclave 2 / cellulose composite hydrogel for CO 2 Supercritical drying treatment, the set temperature and pressure of the autoclave are 40~45℃ and 6.0~10.0Mpa respectively, and the autoclave is filled with supercritical CO 2 ; Supercritical CO 2 Drying method can effectively avoid TiO 2 The / cellulose composite hydrogels retain their porous structure during the drying process.
[0027] S30, TiO 2 / cellulose composite aerogel was pyrolyzed to obtain TiO 2 / cellulose composite carbon aerogel.
[0028] Specifically, step S30 also includes: The cellulose aerogel was pyrolyzed at 550-650 °C for 1-3 h at a heating rate of 3-5 °C / min in an inert atmosphere to prepare TiO 2 / cellulose composite carbon aerogel. Precise control of pyrolysis parameters helps to form carbonized products with certain conductivity and specific structure.
[0029] S40, TiO 2 / cellulose composite carbon aerogel as substrate for the growth of Ni 1 Co 3 The nanoneedle array is prepared by washing and drying the obtained precipitate to form a flexible self-supporting supercapacitor electrode material.
[0030] Specifically, step S40 also includes: TiO 2 / cellulose composite carbon aerogel impregnated with three-dimensional Ni 1 Co 3 The hydroxide nanoneedle precursor is subjected to water bath heating treatment, and the precipitate after the reaction is completed is washed and dried multiple times to obtain a flexible self-supporting supercapacitor electrode material.
[0031] Specifically, TiO 2 / cellulose composite carbon aerogel and three-dimensional Ni 1 Co 3 The mass ratio of the hydroxide nanoneedle precursor is 1: (280~320); the three-dimensional Ni 1 Co 3 The hydroxide nanoneedle precursor is Ni(NO 3 ) 2 6H 2 O、Co(NO 3 ) 2 6H 2 O, urea and water are mixed in a mass ratio of 1:3:(2~4):(100~120); the heating temperature of the water bath heating treatment is 115~125℃, and the heating time is 5~6h.
[0032] In a second aspect, the present invention further provides a flexible self-supporting supercapacitor electrode material, which is prepared by any of the above methods for preparing a flexible self-supporting supercapacitor electrode material.
[0033] The technical solution of the present invention is now further described in conjunction with specific embodiments.
[0034] Embodiment 1: This embodiment 1 provides a method for preparing a flexible self-supporting supercapacitor electrode material, which specifically includes: Step (1): Prepare 100 g of 2.5% by mass bamboo carboxylated nanocellulose solution and 0.5 g of TiO2 The nanotubes were mixed after magnetic stirring, and then ultrasonically dispersed by an ultrasonic cell disruptor in an ice bath for 20 min and then allowed to stand at room temperature for 12 h to obtain TiO 2 / cellulose composite hydrogel.
[0035] Step (2): Use an autoclave to heat TiO 2 The TiO 2 / cellulose composite aerogel; wherein the set temperature and pressure of the autoclave are 45°C and 8.0 MPa respectively, and the autoclave is filled with supercritical CO 2 .
[0036] Step (3): In an inert atmosphere, 2 / cellulose composite aerogel was pyrolyzed to obtain TiO 2 / cellulose composite carbon aerogel; wherein the inert atmosphere is Ar, the heating rate of the pyrolysis treatment is 3°C / min, the pyrolysis temperature is 600°C, and the pyrolysis time is 3h.
[0037] Step (4): Ni(NO 3 ) 2 6H 2 O、Co(NO 3 ) 2 6H 2 O, urea and water were mixed in a mass ratio of 1:3:3:113 to prepare a total of 120 g of solution, and then the prepared solution was transferred to a Teflon-lined autoclave to sterilize TiO 2 The 3D Ni / cellulose composite carbon aerogel was immersed in the reaction solution and hydrothermally treated at 120 °C for 6 h. After the reaction was completed, the precipitate was washed with deionized water 3 times and then dried at 60 °C for 12 h to obtain a 3D Ni 1 Co 3 -OH@Carbon gas condensation hybrid nanomaterials.
[0038] Embodiment 2: This embodiment 2 provides a method for preparing a flexible self-supporting supercapacitor electrode material, which specifically includes: Step (1): Prepare 200 g of 3% by mass bamboo carboxylated nanocellulose solution and 1.6 g of TiO 2 The nanotubes were mixed after magnetic stirring, and then ultrasonically dispersed by an ultrasonic cell disruptor in an ice bath for 30 min and then allowed to stand at room temperature for 18 h to obtain TiO 2 / cellulose composite hydrogel.
[0039] Step (2): Use an autoclave to heat TiO 2 The TiO 2 / cellulose composite aerogel; wherein the set temperature and pressure of the autoclave are 45°C and 8.0 MPa respectively, and the autoclave is filled with supercritical CO 2 .
[0040] Step (3): In an inert atmosphere, 2 / cellulose composite aerogel was pyrolyzed to obtain TiO 2 / cellulose composite carbon aerogel; wherein the inert atmosphere is Ar, the heating rate of the pyrolysis treatment is 5°C / min, the pyrolysis temperature is 650°C, and the pyrolysis time is 3h.
[0041] Step (4): Ni(NO 3 ) 2 6H 2 O、Co(NO 3 ) 2 6H 2 O, urea and water were mixed in a mass ratio of 1:3:4:112 to prepare a total of 300 g of solution, which was then transferred to a Teflon-lined autoclave to sterilize the TiO 2 The 3D Ni / cellulose composite carbon aerogel was immersed in the reaction solution and hydrothermally treated at 125 °C for 5 h. After the reaction was completed, the precipitate was washed with deionized water 3 times and then dried at 50 °C for 12 h to obtain a 3D Ni 1 Co 3 -OH@Carbon gas condensation hybrid nanomaterials.
[0042] Embodiment 3: This embodiment 3 provides a method for preparing a flexible self-supporting supercapacitor electrode material, which specifically includes: Step (1): Prepare 300 g of 2% by mass bamboo carboxylated nanocellulose solution and 1.5 g of TiO 2 The nanotubes were mixed after magnetic stirring, and then ultrasonically dispersed by an ultrasonic cell disruptor in an ice bath for 10 min and then allowed to stand at room temperature for 24 h to obtain TiO 2 / cellulose composite hydrogel.
[0043] Step (2): Use an autoclave to heat TiO 2 The TiO 2 / cellulose composite aerogel; wherein the set temperature and pressure of the autoclave are 45°C and 8.0 MPa respectively, and the autoclave is filled with supercritical CO 2 .
[0044] Step (3): In an inert atmosphere, 2 / cellulose composite aerogel was pyrolyzed to obtain TiO 2 / cellulose composite carbon aerogel; wherein the inert atmosphere is Ar, the heating rate of the pyrolysis treatment is 3°C / min, the pyrolysis temperature is 570°C, and the pyrolysis time is 3h.
[0045] Step (4): Ni(NO 3 ) 2 6H 2 O、Co(NO 3 ) 2 6H 2 O, urea and water were mixed in a mass ratio of 1:3:2:114 to prepare a total of 500 g of solution, which was then transferred to a Teflon-lined autoclave to sterilize the TiO 2 The 3D Ni / cellulose composite carbon aerogel was immersed in the reaction solution and hydrothermally treated at 115 °C for 6 h. After the reaction was completed, the precipitate was washed with deionized water 5 times and then dried at 60 °C for 18 h to obtain a 3D Ni 1 Co 3 -OH@Carbon gas condensation hybrid nanomaterials.
[0046] Comparative Example 1: Comparative Example 1 provides a method for preparing a flexible self-supporting supercapacitor electrode material, which is substantially the same as the method of Example 1, except that: Step (1): prepare 100 g of a 2.5% by mass bamboo carboxylated nanocellulose solution, then ultrasonically disperse it in an ice bath for 20 minutes using an ultrasonic cell disruptor and then stand it at room temperature for 12 hours to obtain a cellulose hydrogel with the same concentration as in the example.
[0047] The preparation method of comparative example 1 uses cellulose hydrogel to carry out the subsequent steps (2) to (4) to obtain a three-dimensional Ni 1 Co 3 -OH@Carbon gas condensation hybrid nanomaterials.
[0048] Comparative Example 2: Comparative Example 2 provides a method for preparing a flexible self-supporting supercapacitor electrode material, which is substantially the same as the method of Example 1, except that: Step (1): Prepare 100 g of 2.5% mass fraction carboxylated nanocellulose solution made of poplar pulp and 0.5 g of TiO 2 The nanotubes were mixed after magnetic stirring, and then ultrasonically dispersed by an ultrasonic cell disruptor in an ice bath for 20 min and then allowed to stand at room temperature for 12 h to obtain TiO 2 / cellulose composite hydrogel.
[0049] Comparative Example 3: Comparative Example 3 provides a method for preparing a flexible self-supporting supercapacitor electrode material, which is substantially the same as the method of Example 1, except that: Step (1): Prepare 100 g of 2.5% by mass bamboo carboxylated nanocellulose solution and 1 g of TiO 2 Nanotubes were mixed after magnetic stirring (TiO 2 The mass ratio of nanotubes to bamboo carboxylated nanocellulose was 0.4:1), and then ultrasonic cell disruptor was used for 20 min in an ice bath and then allowed to stand at room temperature for 12 h to obtain TiO 2 / cellulose composite hydrogel.
[0050] Comparative Example 4: Comparative Example 4 provides a method for preparing a flexible self-supporting supercapacitor electrode material, which is substantially the same as the method of Example 1, except that: Step (1): prepare 100 g of a 2.5% by mass bamboo carboxylated nanocellulose solution and 0.5 g of carbon nanotubes, mix them with magnetic stirring, and then ultrasonically disperse them for 20 minutes using an ultrasonic cell disruptor in an ice bath and stand them at room temperature for 12 hours to obtain a carbon-loaded cellulose composite hydrogel.
[0051] The preparation method of comparative example 4 uses carbon-loaded cellulose composite hydrogel to carry out subsequent steps (2) to (4) to obtain a three-dimensional Ni 1 Co 3 -OH@Carbon gas condensation hybrid nanomaterials.
[0052] Comparative Example 5: Comparative Example 5 provides a single metal hydroxide Co(OH) 2 @The preparation method of carbon gas condensation hybrid nanomaterial is roughly the same as the preparation method of this embodiment 1, except that: Step (4): Co(NO 3 ) 2 6H 2 O、NH 4 F. Urea and water were mixed in a mass ratio of 3:0.3:3:113.7 to prepare a total of 120 g of solution. The prepared solution was then transferred to a Teflon-lined autoclave and the TiO 2 The / cellulose composite carbon aerogel was immersed in the reaction solution and hydrothermally treated at 120 °C for 6 hours. After the reaction was completed, the precipitate was washed with deionized water 3 times and then dried at 60 °C for 12 hours to obtain the single metal hydroxide Co(OH) 2 @Carbon gas condensation hybrid nanomaterials.
[0053] Comparative Example 6: Comparative Example 6 provides a method for preparing a flexible self-supporting supercapacitor electrode material, which is substantially the same as the method of Example 1, except that: Step (4): Ni(NO 3 ) 2 6H 2 O、Co(NO 3 ) 2 6H 2 O, urea and water were mixed in a mass ratio of 1:3:3:113 to prepare a total of 120 g of solution, and then the prepared solution was transferred to a Teflon-lined autoclave to sterilize TiO 2 The 3D Ni / cellulose composite carbon aerogel was immersed in the reaction solution and hydrothermally treated at 100 °C for 5 h. After the reaction was completed, the precipitate was washed with deionized water 3 times and then dried at 60 °C for 12 h to obtain a 3D Ni 1 Co 3 -OH@Carbon gas condensation hybrid nanomaterials.
[0054] Specifically, the surface micromorphology of the supercapacitor electrode materials prepared by using Examples 1 to 3 and Comparative Examples 1 to 6 was observed using a Nanosem 430 field emission scanning electron microscope produced by Philips of the Netherlands.
[0055] Specifically, the mechanical properties of the aerogel were measured using a Z020 universal material testing machine. The experiment used a compression test, with an elastic modulus test rate of 2 mm / min and a compression deformation of 50%.
[0056] Specifically, a physical adsorption analyzer (ASAP2460, 77K) was used to obtain nitrogen adsorption / desorption isotherms. Before the test, the sample was heated in vacuum at 473K for 10 hours to completely remove the physically adsorbed molecules in the sample. The specific surface area of the sample was calculated according to the BET (Brunauer-Emmett-Teller) theoretical method, and the pore size distribution of the sample was calculated by the BJH (Barrett-Joyner-Halenda) model.
[0057] Specifically, the cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves of the samples were tested using a Shanghai Chenhua 760C electrochemical workstation. A three-electrode device was used for the test. The prepared sample was the working electrode, the platinum sheet was the counter electrode, mercurous chloride was the reference electrode, and the electrolyte was potassium hydroxide (KOH) with a concentration of 6M.
[0058] See also Figure 2A to Figure 2B , Figure 2A to Figure 2B In the method for preparing the flexible self-supporting supercapacitor electrode material provided in Example 1 of the present invention, TiO 2SEM (Scanning Electron Microscope) image of / cellulose composite carbon aerogel; Figure 2A to Figure 2B It can be seen that the cellulose in the cellulose composite carbon aerogel is TiO 2 Nanotubes are used as a skeleton for winding and cross-linking, and a three-dimensional network pore structure is successfully constructed. This network structure can ensure effective ion transport and electron transfer during the electrochemical reaction.
[0059] See also Figure 3A to Figure 3B , Figure 3A to Figure 3B The three-dimensional Ni provided in Example 1 of the present invention 1 Co 3 Preparation method of three-dimensional Ni-OH@ carbon gas condensation hybrid nanomaterials 1 Co 3 -OH@ carbon gas condensation hybrid nanomaterials SEM images; Figure 3A to Figure 3B It can be seen that Ni 1 Co 3 -OH nanoneedles on TiO 2 / cellulose composite carbon aerogel grows uniformly on the coarse fiber structure.
[0060] See also Figure 4A , Figure 4A The three-dimensional Ni prepared in Example 1 of the present invention 1 Co 3 -OH@Carbon gas condensation hybrid nanomaterial cyclic voltammetry curve; It is the cyclic voltammetry curve of the electrode material sample obtained at different scanning speeds (5~50mV), and the voltage range is 0~0.6V; Figure 4A It can be seen that the cyclic voltammetry curve has obvious oxidation peaks and reduction peaks, indicating that this sample has good pseudocapacitive properties.
[0061] See also Figure 4B , Figure 4B The three-dimensional Ni prepared in Example 1 of the present invention 1 Co 3 -OH@Carbon gas condensation hybrid nanomaterial constant current charge and discharge curve; Figure 4B It can be seen that the discharge time is short at a higher current density, but the discharge time is longer at a lower current density. At this time, the specific charge at current densities of 1A / g, 2A / g, 3A / g, 4A / g and 5A / g is 734C / g, 651C / g, 600C / g, 569C / g and 536C / g respectively.
[0062] See also Figure 5 , Figure 5 The three-dimensional Ni prepared in Example 1 of the present invention 1 Co 3-OH@Carbon gas condensation hybrid nanomaterial cyclic stability test diagram; Figure 5 It can be seen that the stability of the sample is 76.0% after 1000 cycles, which is significantly improved compared with conventional pseudocapacitive electrode materials. This is due to the synergistic effect of cellulose carbon aerogel double layer capacitance and Faraday reaction.
[0063] See also Figure 6A to Figure 6B , Fig. 6A A comparison diagram of nitrogen adsorption / desorption isotherm curves of corresponding samples prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention; Figure 6B is a comparison diagram of the pore size distribution of the corresponding samples prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention; Figure 6A to Figure 6B It can be seen that according to the IUPAC (International Union of Pure and Applied Chemistry) classification standards, the nitrogen adsorption / desorption isotherms of the three samples are typical type IV hysteresis loops, with the presence of mesopores or macropores. However, at low relative pressures, the nitrogen adsorption amount increases sharply and a platform area appears, indicating that the three samples contain a large number of micropores at the same time.
[0064] See also Figure 7 , Figure 7 Ni prepared in Comparative Example 6 1 Co 3 -OH@ carbon gas condensation hybrid nanomaterial SEM image; Figure 7 It can be seen that the Ni prepared by hydrothermal treatment at 100°C for 5 hours in Comparative Example 6 1 Co 3 -OH@Carbon gas condensation hybrid nanomaterials: Ni 1 Co 3 -OH accumulates on the cellulose network in the form of irregular points and flakes, and the specific surface area and pore structure are significantly reduced. Although redox reactions can occur, the active sites are reduced and the electrolyte ion channels are blocked.
[0065] Furthermore, the specific charge data (C / g) of the samples prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 6 at current densities of 1 A / g, 2 A / g, 3 A / g, 4 A / g and 5 A / g are shown in Table 1: Table 1
[0066] Specifically, it can be seen from Table 1 that the supercapacitor electrode material prepared in Example 1 has a specific charge of 734 C / g at a current density of 1 A / g; the supercapacitor electrode material prepared in Example 2 has excellent electrochemical performance, and its specific charge is 712 C / g at a current density of 1 A / g; the supercapacitor electrode material prepared in Example 3 has excellent electrochemical performance, and its specific charge is 707 C / g at a current density of 1 A / g; the supercapacitor electrode material prepared in Comparative Example 1 has a specific charge of 352 C / g at a current density of 1 A / g; The supercapacitor electrode material was tested at a current density of 1A / g and its specific charge was 498C / g; the supercapacitor electrode material prepared in Comparative Example 3 was tested at a current density of 1A / g and its specific charge was 549C / g; the supercapacitor electrode material prepared in Comparative Example 4 was tested at a current density of 1A / g and its specific charge was 387C / g; the supercapacitor electrode material prepared in Comparative Example 5 was tested at a current density of 1A / g and its specific charge was 281C / g; the supercapacitor electrode material prepared in Comparative Example 6 was tested at a current density of 1A / g and its specific charge was 331C / g.
[0067] Furthermore, the specific surface areas (m 2 / g), elastic modulus (KPa) and 50% deformation pressure (KPa) are shown in Table 2: Table 2
[0068] Specifically, the specific charge of the supercapacitor electrode material prepared in Comparative Example 1 is significantly lower than that in Examples 1 to 2, which is mainly due to the fact that the reinforcing material TiO is not added in this comparative example. 2 Nanotubes, from the nitrogen adsorption / desorption isotherms and pore size distribution of the sample, it can be seen that the number of micropores and specific surface area are reduced accordingly, and there is not enough space to store charge. At the same time, the lack of TiO 2 Nanotube superhydrophilic pseudocapacitive material leads to a serious decrease in specific charge.
[0069] Specifically, the specific electric capacity of the supercapacitor electrode material prepared in Comparative Example 2 is significantly lower than that of Examples 1 and 2. This is mainly because the elastic modulus, 50% deformation pressure, specific surface area and number of pores of the composite material prepared by changing the type of nanocellulose in the comparative case are significantly reduced. This is because bamboo nanofibers have high aspect ratio, toughness and unique resilience, and have high strength in both longitudinal and transverse directions. Due to the reduction in the number of micropores and the TiO 2 Due to the uniformity of distribution, at a current density of 1A / g, the specific charge of the sample is only 498C / g.
[0070] Specifically, since the TiO 2 The high amount of nanotubes added results in limited cellulose, which cannot entangle the halloysite nanotube skeleton, resulting in loose accumulation of some halloysite nanotubes, ultimately reducing the specific surface area and mechanical properties of the material.
[0071] Specifically, the reinforcing material of Comparative Example 4 is composed of TiO 2 Nanotubes were replaced with carbon nanotubes. Since there are no hydroxyl groups on the surface of carbon nanotubes, they cannot chemically crosslink with bamboo carboxylated nanofibers, and only interact with each other by physical attachment. As a result, although the specific surface area of the sample material of Comparative Example 4 did not decrease significantly, the mechanical properties decreased significantly. Since carbon nanotubes have strong conductivity but no pseudocapacitive properties and the effect of improving the hydrophilicity of the substrate, the comparative electric charge has been improved to a certain extent, but the effect is limited. Therefore, the sample of Comparative Example 4 has a specific electric charge of only 387C / g at a current density of 1A / g.
[0072] Specifically, the electrode material prepared in Comparative Example 5 was tested to have a specific charge of 281C / g at a current density of 1A / g. This is because TiO 2 Nanotube-synergistic dual-species transition metal compounds have higher conductivity and richer redox reactions than single-component transition metal compounds, exhibiting better electrochemical energy storage performance.
[0073] Specifically, the Ni prepared in Comparative Example 6 1 Co 3 -OH@ carbon gas condensation hybrid nanomaterials, Ni 1 Co 3 -OH accumulates on the cellulose network in the form of irregular points and flakes, and the specific surface area and pore structure are significantly reduced. Although redox reactions can occur, the active sites are reduced and the electrolyte ion channels are blocked; therefore, the specific charge of this sample is only 331C / g at a current density of 1A / g.
[0074] The present invention provides a Ni 1 Co 3 -OH@ carbon gas condensation hybrid nanomaterial and its preparation method, the above material is TiO 2 Nanotubes were used as reinforcing materials. The surface hydroxyl groups were tightly connected with the carboxyl groups in the high-strength and high-elastic bamboo nanocellulose through esterification reaction. Composite carbon aerogels were prepared after aging and pyrolysis. 2 Growth of Ni on the network skeleton of / cellulose composite carbon aerogel 1 Co 3 -OH nanoneedles were prepared. 1 Co 3When -OH@carbon gas condensation hybrid nanomaterials are used as flexible self-supporting supercapacitor electrode materials, their specific charge is tested to be 734C / g at a current density of 1A / g; at a current density of 5A / g, after 1000 charge and discharge tests, the material still retains 76.0% of its specific charge.
[0075] The present invention utilizes TiO 2 Nanotubes as reinforcing materials not only increase the strength of flexible electrode materials, but their super-hydrophilic properties also help the rapid diffusion of electrolyte ions at the electrode / electrolyte interface. At the same time, the addition of titanium dioxide nanotubes enriches the micro-mesoporous structure of the composite carbon aerogel, allowing for a larger specific surface area and number of micropores to store charge. Finally, the double metal hydroxide grown on the carbon aerogel substrate fiber by a hydrothermal method increases the specific charge of the flexible electrode material. A supercapacitor electrode material with high specific capacitance, flexibility and certain support capacity is prepared.
[0076] Compared with the prior art, the present invention has the following advantages: (1) The present invention uses one-dimensional bamboo carboxylated nanocellulose prepared by the etherification method, which has higher strength and elastic modulus and easier weaving than other cellulose resources. The prepared three-dimensional carbon aerogel has the characteristics of light weight, high elasticity and stable structure, ensuring the flexibility of the electrode material.
[0077] (2) The present invention utilizes TiO with good mechanical properties 2 Nanotubes act as reinforcing materials, increasing the strength of flexible electrode materials, making them less prone to breakage or structural collapse when subjected to external forces.
[0078] (3) TiO 2 The superhydrophilic property of nanotubes facilitates the rapid diffusion of electrolyte ions at the electrode / electrolyte interface. After pyrolysis treatment, they transform from an amorphous form to anatase. The oxygen vacancies on the surface can easily dissociate water, achieving chemical adsorption of water.
[0079] (4) TiO 2 The addition of nanotubes enriches the micro-mesoporous structure of the composite carbon aerogel, resulting in a larger specific surface area and a larger number of micropores for storing charges.
[0080] (5) The double metal hydroxide grown on the carbon aerogel substrate fiber by the hydrothermal method improves the specific charge capacity of the flexible electrode material. Compared with the single metal hydroxide, the synergistic effect of the two different metal ions improves its performance advantages.
[0081] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.
[0082] The above embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a flexible self-supporting supercapacitor electrode material, characterized in that: include: S10, mixing the bamboo carboxylated nanocellulose solution with the TiO2 nanotubes and performing an ice bath ultrasonic dispersion treatment, and obtaining a TiO2 / cellulose composite hydrogel after standing at room temperature; S20, subjecting the TiO2 / cellulose composite hydrogel to a CO2 supercritical drying treatment to obtain a TiO2 / cellulose composite aerogel; S30, pyrolyzing the TiO2 / cellulose composite aerogel under an inert atmosphere to obtain a TiO2 / cellulose composite carbon aerogel; S40, growing a Ni1Co3 nanoneedle array using the TiO2 / cellulose composite carbon aerogel as a substrate, and preparing a flexible self-supporting supercapacitor electrode material by washing and drying the obtained precipitate.
2. The method for preparing a flexible self-supporting supercapacitor electrode material according to claim 1, characterized in that: In the step S10: the bamboo carboxylated nanocellulose in the bamboo carboxylated nanocellulose solution is prepared by an etherification method; the cross-sectional size of the bamboo carboxylated nanocellulose is 5-10 nm, the length is 500-1000 nm, and the aspect ratio is (50:1)-(50:1); the mass fraction of the bamboo carboxylated nanocellulose solution is 2%-3%.
3. The method for preparing a flexible self-supporting supercapacitor electrode material according to claim 1, characterized in that: In the step S10: the surface of the TiO2 nanotube has hydroxyl groups, the outer diameter is 10-200 nm, and the length is 1-50 um; the mass ratio of the TiO2 nanotube to the bamboo carboxylated nanocellulose is (2-3):
10.
4. The method for preparing a flexible self-supporting supercapacitor electrode material according to claim 1, characterized in that: In the step S10, the ultrasonic dispersion time of the ice bath ultrasonic dispersion treatment is 10 to 30 minutes, and the standing time at room temperature is 12 to 24 hours.
5. The method for preparing a flexible self-supporting supercapacitor electrode material according to claim 1, characterized in that: In the step S20: the drying temperature for CO2 supercritical drying is 40-45°C, and the drying pressure is 6.0-10.0 MPa.
6. The method for preparing a flexible self-supporting supercapacitor electrode material according to claim 1, characterized in that: In the step S30: the heating rate of the pyrolysis treatment is 3-5°C / min, the pyrolysis temperature is 550-650°C, and the pyrolysis time is 1-3h.
7. The method for preparing a flexible self-supporting supercapacitor electrode material according to claim 1, characterized in that: The S40 step specifically includes: immersing the TiO2 / cellulose composite carbon aerogel into a three-dimensional Ni1Co3 hydroxide nanoneedle precursor for water bath heating treatment, and after the reaction is completed, the precipitate is washed and dried multiple times to obtain the flexible self-supporting supercapacitor electrode material.
8. The method for preparing a flexible self-supporting supercapacitor electrode material according to claim 7, characterized in that: The mass ratio of the TiO2 / cellulose composite carbon aerogel to the three-dimensional Ni1Co3 hydroxide nanoneedle precursor is 1:(280~320); the three-dimensional Ni1Co3 hydroxide nanoneedle precursor is formed by mixing Ni(NO3)2·6H2O, Co(NO3)2·6H2O, urea and water in a mass ratio of 1:3:(2~4):(100~120); the heating temperature of the water bath heating treatment is 115~125°C, and the heating time is 5~6h.
9. A flexible self-supporting supercapacitor electrode material, characterized in that: The flexible self-supporting supercapacitor electrode material is prepared by the preparation method of the flexible self-supporting supercapacitor electrode material according to any one of claims 1 to 8.